Antimicrobial Activity of Gels Supplemented With Nanoparticles as Intracanal Medication in Endodontics: A Systematic Review and Meta-Analysis of In Vitro, In Vivo, and RCT Studies - Pedro Rosales García; Eva Concepción Aguirre López; José Eduardo Pérez Romano; Jorge Humberto Luna Domínguez; Nuria Patiño Marín; Alan Martínez Zumarán; Idania De Alba Montero; Marco Felipe Salas Orozco (Journal of Nanotechnology)
Conclusions: Gels supplemented with nanoparticles show potential antimicrobial efficacy in vitro, but the evidence from clinical trials is inconsistent. High heterogeneity and potential publication bias indicate the need for more standardized clinical research to accurately assess the effectiveness of nanoparticle-supplemented gels in endodontic treatment.